Knowledge management in sport mega-events: A systematic literature review - Qin, Yuan; Rocha, Claudio M.; Morrow, Stephen (Frontiers in Sports and Active Living, 2022)
Introduction The aim of this study was to conduct a systematic review to describe and explore the current state-of-the-art of sport mega-event knowledge management research. Methods Following the PRISMA protocol, the authors conducted a systematic search of academic and gray literature in sport, social sciences, and humanities databases. From the initial 1,751 studies reviewed, 16 met the inclusion criteria. Findings In these studies, knowledge management in sport mega-events was mainly researched in the context of the Olympic Games. Compared with other events, the Olympic Games built a more formal knowledge management programme, which may explain why it attracted more attention. Discussion Most of the studies highlighted the importance of tacit knowledge and individuals, as well as the needs of different stakeholder groups. Findings showed that social, cultural, political, and historical differences between hosts weaken the effect of knowledge management. Many of the published empirical studies are descriptive investigations and lack support of related theories or conceptual frameworks. The impacts of knowledge management process on the host regions and knowledge transfer between events and local stakeholders have been little explored.